Peningkatan Keterampilan Berpikir Kritis Melalui Pembelajaran Inovatif-Progresif Pelajaran PAI Dan Budi Pekerti Siswa Kelas 4 - Siti Umiyati; Muhmmad Mahfud; Desy Rahmayanti Khumairo (Jurnal Pendidikan Agama Islam Miazhar, 2023)
Based on the phenomenon observed at SDN Putat Jaya 1/377 Surabaya, the students' learning outcomes are still not optimal, with 57% of the students not achieving proficiency and requiring improvement. Essentially, various instructional activities implemented by teachers so far have been related to cognitive enhancement efforts, but have not specifically targeted critical thinking skills. The implementation of the Innovative Progressive Learning Model in PAI (Islamic Education) and Budi Pekerti (Character Education) activities has been found to significantly improve students' critical thinking abilities, particularly in the fourth grade, with a remarkable increase in student proficiency by 42.86%. The students' critical thinking skills in the second cycle reached 88, surpassing the minimum performance indicator for teacher performance evaluation set at 85%. Students' response to the innovative progressive learning approach has also been highly positive, with 97% of students feeling comfortable and actively engaged. Moreover, there has been a notable increase in students' academic achievements, with scores rising by 9 points from 76 to 85, indicating proficiency as 89% of students have exceeded the Minimum Completion Criteria (KKM) of 85. The implementation of the Innovative Progressive Learning Model followed the planned Lesson Implementation Plan (RPP) smoothly and accordingly.